Do the Dynamics of Prior Information Depend on Task Context? An Analysis of Optimal Performance and an Empirical Test - van Ravenzwaaij, Don; Mulder, Martijn; Tuerlinckx, Francis; Wagenmakers, Eric-Jan (Frontiers in Psychology, 2012)
In speeded two-choice tasks, optimal performance is prescribed by the drift diffusion model. In this model, prior information or advance knowledge about the correct response can manifest itself as a shift in starting point or as a shift in drift rate criterion. These two mechanisms lead to qualitatively different choice behavior. Analyses of optimal performance (i.e., Bogacz, Brown, Moehlis, Holmes, & Cohen, 2006; Hanks, Mazurek, Kiani, Hopp, & Shadlen, 2011) have suggested that bias should manifest itself in starting point when difficulty is fixed over trials, whereas bias should (additionally) manifest itself in drift rate criterion when difficulty is variable over trials. In this article, we challenge the claim that a shift in drift criterion is necessary to perform optimally in a biased decision environment with variable stimulus difficulty. This paper consists of two parts. Firstly, we demonstrate that optimal behavior for biased decision problems is prescribed by a shift in starting point, irrespective of variability in stimulus difficulty. Secondly, we present empirical data which show that decision makers do not adopt different strategies when dealing with bias in conditions of fixed or variable across-trial stimulus difficulty. We also perform a test of specific influence for drift rate variability.